2007
DOI: 10.1007/s10265-006-0056-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium chloride on the response of the halophyte species Sesuvium portulacastrum grown in mannitol-induced water stress

Abstract: Sesuvium portulacastrum is a halophytic species well adapted to salinity and drought. In order to evaluate the physiological impact of salt on water deficit-induced stress response, we cultivated seedlings for 12 days, in the presence or absence of 100 mmol l(-1) NaCl, on a nutrient solution containing either 0 mmol l(-1) or 25 mmol l(-1) mannitol. Mannitol-induced water stress reduced growth, increased the root/shoot ratio, and led to a significant decrease in water potential and leaf relative water content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 33 publications
5
45
0
1
Order By: Relevance
“…The development of the root system increases the water absorption and maintains the osmotic pressure. An increase in the root system under water stress has been reported in sunflower (Tahir et al, 2002), and in Sesuvium portulacastrum (Slama et al, 2007). Water deficit reduces the growth of leaves more compared to roots because the growth of roots and leaves exhibits different sensitivities to reduced Badri et al 1347 water availability (Verslues et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of the root system increases the water absorption and maintains the osmotic pressure. An increase in the root system under water stress has been reported in sunflower (Tahir et al, 2002), and in Sesuvium portulacastrum (Slama et al, 2007). Water deficit reduces the growth of leaves more compared to roots because the growth of roots and leaves exhibits different sensitivities to reduced Badri et al 1347 water availability (Verslues et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in the number as well as the biomass of leaves suggest that net CO 2 assimilation (A) per unit of leaf area is higher in plants subjected to drought stress than those grown in non-limiting conditions. Accordingly, Slama et al (2007) reported a decrease of number and size of leaves and an increase in net CO 2 assimilation in leaf growth rate per unit under water deficit in S. portulacastrum. This reduction saves water for the plant and is therefore considered as a criterion for adaptation to drought.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work demonstrated in a halophyte Sesuvium portulacastrum increased sweating during salt stress [22]. [6] showed that the loss of water by transpiration increased mineral absorption in plants.…”
Section: Stress In Seawatermentioning
confidence: 99%
“…This abiotic stress causes desertification coupled with a progressive decrease of vegetation coverage and rapid soil degradation in arid and semi-arid regions (Slama et al 2007;Ma et al 2012). Since most crops are highly susceptible to drought, xerophytes, such as Haloxylon ammodendron (C. A.…”
Section: Introductionmentioning
confidence: 99%